Prevalence of low molecular weight proteinuria and Dent Disease 1 CLCN5 mutations in proteinuric cohorts - Beara-Lasic, Lada (Pediatr Nephrol, 2019)
BACKGROUND: Dent disease type 1 (DD1) is a rare X-linked disorder caused mainly by CLCN5 mutations. Patients may present with nephrotic range proteinuria leading to erroneous diagnosis of focal segmental glomerulosclerosis (FSGS) and unnecessary immunosuppressive treatments. METHODS: The following cohorts were screened for CLCN5 mutations: Chronic Kidney Disease in Children (CKiD; n=112); Multicenter FSGS-Clinical Trial (FSGS-CT) (n=96) and Novel therapies for resistant FSGS Trial (FONT) (n=30). Urinary α(1)-microglobulin (α(1)-M), albumin (A), total protein (TP) and creatinine (Cr) were assessed from CKiD subjects (n=104); DD1 patients (n=14) and DD1 carriers (DC; n=8). TP/Cr, α1M/Cr, α1M/TP and A/TP from the CKiD cohort were compared with DD1 and DC. RESULTS: No CLCN5 mutations were detected. TP/Cr was lower in DC and CKiD with tubulointerstitial disease than DD1 and CKiD with glomerular disease (P < 0.002). α(1)M/Cr was higher in DD1 than CKiD and DC (P < 0.001). A/TP was lower in DD1, DC and CKiD with tubulointerstitial disease, higher in CKiD with glomerular disease (P < 0.001). Thresholds for A/TP of ≤ 0.21 and α(1)-M/Cr ≥ 120 mg/g (> 13.6 mg/mmol) creatinine were good screens for Dent disease. CONCLUSIONS: CLCN5 mutations were not seen in screened CKiD/FSGS cohorts. In our study, a cut off of TP/Cr > 600 mg/g (> 68 mg/mmol) and A/TP < 0.3 had a high sensitivity and specificity to distinguish DD1 from both CKiD glomerular and tubulointerstitial cohorts. α(1)-M/Cr ≥ 120 mg/g (> 13.6 mg/mmol) had the highest sensitivity and specificity when differentiating DD1 and studied CKiD populations.